A systematic review of optimal pharmacokinetic/pharmacodynamic parameters for beta-lactam therapy in infective endocarditis. (24th January 2023) - Robson, Christopher; Tan, Bryan; Stuart, Rhonda; Nicholls, Stephen; Rogers, Benjamin A; Sandaradura, Indy
Abstract: Background: Beta-lactam antibiotics are the mainstay of therapy for most bacterial causes of infective endocarditis (IE). Traditionally considered as agents with a broad therapeutic index, there is increasing recognition that standard doses may be subtherapeutic or toxic in critically ill patients. Optimizing therapy for efficacy requires a defined pharmacokinetic (PK)/pharmacodynamic (PD) target associated with clinical and microbiological cure. Objectives: To elucidate the factors that influence beta-lactam PK and PD variability in IE and to examine optimal PK/PD target parameters for therapy. Methods: The review was conducted in accordance with Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Clinical and laboratory in vivo animal or human studies examining PK and/or PD of beta-lactam antibiotics in IE were eligible. Ovid MEDLINE, Embase and Cochrane Central Registry were searched using defined terms. The Office of Health Assessment and Translation (OHAT) tool was used for assessing risk of bias. Results: From 2677 abstracts, 62 articles were selected for review and synthesis, comprising: 45 animal studies investigating the broad categories of beta-lactam diffusion into vegetations, PK/PD determinants of outcome, mode of antibiotic delivery and synergistic impact of agents; and 17 human studies totalling 347 participants. Findings supported the importance of time-dependent killing for beta-lactams but heterogeneous data limited the determination of an optimal PK/PD target for IE treatment. Conclusion: Beta-lactam PK and PD in endocarditis are variable and specific to the particular antibiotic-organism combination. Time-dependent killing is important, consistent with non-endocarditis studies, but there is little agreement on optimal drug exposure. Clinical studies examining PK/PD targets in endocarditis are required to further inform drug selection and dosing.